Transjugular Liver Biopsy: The Key to a Rare Etiology of Cholestatic Hepatitis after Bone Marrow Transplantation - Pestana,Inês (2024)
Abstract Introduction: Hematopoietic stem cell transplantation (HSCT) is associated with multiple complications, such as sinusoidal obstruction syndrome (SOS) (hepatomegaly, ascites, jaundice, and thrombocytopenia) and graft-versus-host disease (GVHD) (with the skin, gastrointestinal tract, and liver being the main targets). These entities may present overlapping clinical ﬁndings, being considered differential diagnoses, but their coexistence is rare. Case Presentation: A 29-year-old male with acute myeloid leukemia underwent HSCT. On day (D)+20, he developed hyperbilirubinemia, pleural effusion, ascites, and painful hepatomegaly. Abdominal ultrasound was suggestive of SOS, and deﬁbrotide was initiated. On D+44, acute cutaneous, intestinal, and hepatic GVHD developed which improved after treatment with methylprednisolone. On D+132, there was worsening cholestasis and abdominal pain. MRCP revealed strictures in several segments of the intrahepatic bile ducts and irregularity of the main bile duct. Due to aggravation of liver enzyme changes and clinical worsening, he was admitted to the Intensive Care Unit. Due to persistence of severe hyperbilirubinemia (30 mg/dL) and thrombocytopenia (30,000 cell/uL), he underwent a hepatic hemodynamic study which revealed a hepatic venous pressure gradient of 10 mm Hg. The transjugular liver biopsy revealed canalicular hepatic cholestasis, bile duct injury, and focal hepatocellular necrosis suggestive of GVHD as well as injury to centrilobular veins and centrilobular necrosis compatible with possible SOS. Mycophenolate mofetil was started, but on D+195, the patient died of septic shock. Discussion/Conclusion: This case is notable for its complexity and for demonstrating the rare coexistence of histological features of SOS and GVHD. Although the clinical and laboratory ﬁndings may be sufﬁcient for the diagnosis, it is important to highlight the importance of liver hemodynamic study and transjugular liver biopsy in these patients who often have severe thrombocytopenia, for the characterization and histological conﬁrmation of cholestatic hepatitis, especially when the etiology may be multifactorial.